Control of Listeria monocytogenes on frankfurters formulated with and without lactate by dipping in sodium lactate and acidified calcium sulfate before and after inoculation for shelf life extension - Stohs, Buffy Ann (Kansas State University, 2009)
The objectives of these studies were to determine the antimicrobial effects of sodium lactate (SL) and acidified calcium sulfate (ACS) on frankfurters formulated with and without lactate in the frankfurter formulation. Two studies were performed, one which mimicked home storage, and the other evaluated the effectiveness of SL (12% v/v) and ACS (12% v/v) as antimicrobial dips when used prior to and after inoculation of Listeria monocytogenes on frankfurters formulated without lactate. In the first study, five peeled frankfurters with and without lactate in the formulation were either dipped in SL or in ACS, stabilized for 30 minutes, vacuum packaged and stored for 30 days at 4°C. Controls were also prepared by dipping in 0.1% peptone. After 30 days the packages were opened and frankfurters were dip inoculated, stabilized for 30 minutes, and one frankfurter from each treatment was sampled. All other frankfurters were then placed in storage at 7°C and sampled after an additional 7, 14, and 21 days. For the second study, treatments consisted of five frankfurters that were first inoculated with a five-strain cocktail of L. monocytogenes, stabilized for 30 minutes, then dipped in SL or acidified ACS; or were first dipped in SL or ACS, stabilized for 30 minutes then dip inoculated. Controls were prepared by dip inoculating frankfurters. One frankfurter from each treatment was sampled immediately. The remaining frankfurters were vacuum packaged, stored at 4°C and sampled after 30, 60, 90, and 120 days. For both studies, on sampling days one frankfurter from each treatment was pulsified and plated on Tryptic Soy Agar (TSA) for viable cell counts and Modified Oxford Medium (MOX) for L. monocytogenes counts. The results indicated that SL dipped frankfurters had lower total aerobic counts and L. monocytogenes counts compared with ACS treatments and the controls. Use of lactate formulation in frankfurters resulted in lower bacterial counts of both natural microflora and inoculated L. monocytogenes in frankfurters after prolonged storage at 4 °C. This research indicates that sodium lactate (12% v/v) may be effective as an antimicrobial dip on frankfurters for the reduction of natural microflora and L. monocytogenes.
Keywords: Listeria monocytogenes; sodium lactate; acidified calcium sulfate; frankfurters; organic acids; Agriculture, Food Science and Technology (0359)